Approximation of the classes B^Ω_p, θ of periodic functions of many variables by Fourier sums in the space L_p with p = 1, ∞ - Myronyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain an exact-order estimate for the deviation of Fourier sums of periodic functions of many variables from the classes B^Ω_p, θ in the space L_p for p = 1, ∞.